2022
DOI: 10.3389/fgene.2022.852429
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Novel Variants on the CHD7 Gene: A Case Series of CHARGE Syndrome

Abstract: Background: CHARGE syndrome (CS) is a single-gene genetic disorder with multiple organ malformations caused by a variant of the chromodomain helicase DNA-binding protein 7 (CHD7) gene on chromosome 8q12.1. In this study, we aimed to investigate new variants that have emerged in these cases compared with typical CS and the relationship between the genes and phenotypes.Methods: Patients with suspected genetic diseases were subjected to Whole Exome Sequencing (WES) at a genetics laboratory in Guangzhou. The avera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
(30 reference statements)
0
6
0
Order By: Relevance
“…Of note, deleterious loss-of function CHD7 mutations interrupt the regulation of gene expression and result in disordered neural crest development [ 41 ]. CHD7 gene mutations are considered to be the genetic cause of over 90 % of patients with typical CHARGE syndrome [ [42] , [43] , [44] ]. Therefore, identifying each novel pathogenic mutation of CHD7 gene, expanding the mutational spectrum, and incorporating it into the database is beneficial for the diagnosis of CHARGE syndrome and estimating the prevalence of the disease [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Of note, deleterious loss-of function CHD7 mutations interrupt the regulation of gene expression and result in disordered neural crest development [ 41 ]. CHD7 gene mutations are considered to be the genetic cause of over 90 % of patients with typical CHARGE syndrome [ [42] , [43] , [44] ]. Therefore, identifying each novel pathogenic mutation of CHD7 gene, expanding the mutational spectrum, and incorporating it into the database is beneficial for the diagnosis of CHARGE syndrome and estimating the prevalence of the disease [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Frameshift and nonsense variants in CHD7 are most commonly identified in CHARGE syndrome, accounting for more than 63% of reported variants between 2004 and 2015 (Alazami et al, 2008; Aramaki et al, 2006; Delahaye et al, 2007; Jongmans et al, 2006; Jyonouchi et al, 2009; Lalani et al, 2006; Legendre et al, 2017; McMain et al, 2008; Tellier et al, 1998; Wincent et al, 2009; Zentner et al, 2010). Similarly, the ClinVar and CHD7 gene databases (http://www.chd7.org) shows that 75% of the 1054 pathogenic and likely pathogenic variants are frameshift (44%) or nonsense (31%) (Wu et al, 2022). Our combined rate of 59% of frameshift (37%) and nonsense (22%) variants was lower than the previously published studies as well as the gene databases.…”
Section: Discussionmentioning
confidence: 99%
“…CHD7.org) shows that 75% of the 1054 pathogenic and likely pathogenic variants are frameshift (44%) or nonsense (31%) (Wu et al, 2022).…”
Section: Genetic Analysismentioning
confidence: 99%
“…The CHD7 gene encodes an ATP‐dependent chromodomain helicase DNA‐binding (CHD) protein that plays a significant role in cell proliferation and neuronal differentiation (Cardoso et al., 2021). In humans, many disease‐associated variants have been discovered in this gene associated with CHARGE syndrome and most of them arose de novo (van Ravenswaaij‐Arts & Martin, 2017; Wu et al., 2022). In addition, other studies, also in humans, have shown that de novo variants in the CHD7 gene are associated with congenital heart disease, the most common type of congenital defect (Homsy et al., 2015; Ji et al., 2020; Patt et al., 2023; Sevim et al., 2020).…”
Section: Analyses Of the De Novo Gene Listmentioning
confidence: 99%